2011
DOI: 10.1007/s00405-011-1642-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome in patients with advanced head and neck cancer: surgery and reconstruction with free flaps versus primary radiochemotherapy

Abstract: The objective was to compare functional outcome in patients with advanced head and neck cancer (HNC) treated with (a) surgical resection and reconstruction with microvascular free flaps (MVFF) followed by radiochemotherapy versus (b) primary radiochemotherapy (RCT) on the basis of the International Classification of Functioning, Disability and Health (ICF) from WHO. This was a cross-sectional, multi-institutional study. The outcome measures included ICF Core Sets for HNC, the EORTC-QLQ, modules c30 + hn35 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
2
20
0
5
Order By: Relevance
“…In this study, health-related QOL was evaluated using the QLQ-C30, QLQ-HN35, and UW-QOL, as in previous studies. 2,3,5,6,8,14,16,17 Our QLQ-C30 results are similar to those reported by Crombie et al 3 and Ch'ng et al 16 for oral SCC and to those reported by Tribius et al 17 for head and neck SCC. The global health status scores obtained in this study are similar to those reported in a previous study of patients with head and neck cancer.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, health-related QOL was evaluated using the QLQ-C30, QLQ-HN35, and UW-QOL, as in previous studies. 2,3,5,6,8,14,16,17 Our QLQ-C30 results are similar to those reported by Crombie et al 3 and Ch'ng et al 16 for oral SCC and to those reported by Tribius et al 17 for head and neck SCC. The global health status scores obtained in this study are similar to those reported in a previous study of patients with head and neck cancer.…”
Section: Discussionsupporting
confidence: 81%
“…5,8 Each item is scored on a 0-100 scale. 3,14 Given the small number of QOL studies in patients with head and neck cancer, an expansion of knowledge about QOL assessment in patients undergoing cancer treatment is needed. 15 Therefore, the aim of this study was to evaluate the health-related QOL of patients with squamous cell carcinoma (SCC) according to tumor location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of radiotherapy on the head and neck has been well investigated and becomes obvious in the clinical situation by scarring and tissue fibrosis accompanied by vessel depletion (Bengtson et al 1993;Jones et al 2007). These circumstances lead to a decrease in head and neck mobility and mouth opening, which are strongly correlated with the quality of life of patients, especially if the mandible is affected also (Chambers et al 2004;Tschiesner et al 2011;Airoldi et al 2011;Mücke et al2011). As already indicated in the present study, patients are seriously affected by the side effects of both therapy modalities, surgery and radiotherapy, as a high percentage of patients would be not willing to repeat the performed treatments (30 vs. 28 patients, Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…Clinical, physical, and sociodemographic factors also contribute to patients' outcome after treatment and should be taken into the patients' oncologic concept (Karvonen-Gutierrez et al 2008). Although several questionnaires to assess the quality of life exist, an objective and reproducible assessment of the physiological function in the head and neck region is not available (Rogers et al 2002;Tschiesner et al 2011). For that reason, an objective functional status was developed and examination of different patients undergoing different treatments performed.…”
Section: Introductionmentioning
confidence: 99%